Uniqueness in the Inverse Conductivity Problem for Complex-Valued Lipschitz Conductivities in the Plane - Lakshtanov, Evgeny (2017)
We consider the inverse impedance tomography problem in the plane. Using Bukhgeim's scattering data for the Dirac problem, we prove that the conductivity is uniquely determined by the Dirichlet-to-Neuman map. Read More: http://epubs.siam.org/doi/abs/10.1137/17M1120981